Distribution of Heavy Metals in Bones, Gills, Livers and Muscles of (Tilapia) Oreochromis niloticus from Henshaw Town Beach Market in Calabar Nigeria - A., Edem Christopher; Vincent, Osabor; Grace, Iniama; Rebecca, Etiuma; Joseph, Eke (Pakistan Journal of Nutrition, 2009)
Two sets of samples of commercially important fish species Oreochromis niloticus of size 29 cm and 20 cm respectively were purchased from the Henshaw town beach market in Calabar, Calabar South Local Government Area of Cross River State, Nigeria in October 2007. The concentrations of five heavy metals (Pb, Zn, Cd, As and Hg) in their bones, gills, livers and muscles were determined using flame atomic absorption spectrophotometer. The result showed the heavy metal concentrations in the 29 cm size samples to be Pb (0.069 ppm) Cd (0.019 ppm) and Zn (0.103 ppm) in the bones. Pb (0.173 ppm) Cd (0.049 ppm) and Zn (0.257 ppm) in the livers. Pb (0.053 ppm) Cd (0.015 ppm) Zn (0.079 ppm) in the muscles Pb (0.133 ppm), Cd (0.038 ppm) and Zn (0.198 ppm) in gills. While the 20 cm size samples had Pb (0.067 ppm) Cd (0.019 ppm) and Zn (0.100 ppm) in bones. Pb (0.067 ppm) Cd (0.019 ppm) and Zn (0.099 ppm) in livers. Pb (0.062 ppm) Cd (0.017 ppm) and Zn (0.095 ppm) in muscles and Pb (0.153 ppm) Cd (0.044 ppm) and Zn (0.227 ppm) in gills. Arsenic and mercury were not detected in any of the samples. The result revealed the distribution of the heavy metal in both 29 cm and 20 cm size samples to follow the order Zn> Pb> Cd while the distribution of the heavy metals in the investigated parts (organs) is shown to follow the order livers > gills > bones > muscles for the 29 cm size samples. And Gills > Livers = bones > muscles in the 20 cm size samples. The result also revealed that the 29 cm size samples had higher concentrations of the heavy metals than the 20 cm size samples. The result also showed that the muscle of Tilapia is safer to consumed than the other parts investigated as it has been shown to contain the least concentrations of the heavy metals determined. This reveals the adverse health effect the people in the study area could be exposed to by the consumption of liver, gills and bones of Tilapia which have high levels of these heavy metals.